Perancangan Sistem Informasi Administrasi di Satuan Pendidikan Anak Usia Dini - Warmansyah, Jhoni; Maulana, Ade Novia (UIN Imam Bonjol Padang, 2021)
The administration that is still manual in archiving is one of the problems that is often encountered in PAUD Units. Therefore we need an alternative that can overcome these problems by utilizing information systems. This study aims to design an administrative information system in early childhood education. The method used is Educational Design Research (EDR) limited to a design model with stages; 1) Preliminary research; 2) Prototyping stage; 3) Assessment phase. This research produces an administrative information system design that can be used by PAUD units to process data and present SPP financial reports that are more practical and accurate. Thus the use of information systems in other areas of management can be a concern for managers in Kindergarten.